2014
DOI: 10.1016/j.jss.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Short-term physical inactivity impairs vascular function

Abstract: Introduction Sedentarism, also termed physical inactivity, is an independent risk factor for cardiovascular diseases. Mechanisms thought to be involved include insulin resistance, dyslipidemia, hypertension, and increased inflammation. It is unknown whether changes in vascular and endothelial function also contribute to this excess risk. We hypothesized that short-term exposure to inactivity would lead to endothelial dysfunction, arterial stiffening and increased vascular inflammation. Methods Five healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 70 publications
2
58
1
1
Order By: Relevance
“…Review study 36 has suggested that prolonged uninterrupted periods of being sedentary results in insufficient skeletal muscle contractions, which suppresses lipoprotein lipase activity, blunts triglyceride uptake, reduces HDL-C levels and glucose load, and increases insulin resistance. In addition, prior bedrest studies 38, 39 demonstrated that prolonged sedentary time leads to impaired vascular function manifest as endothelial dysfunction, arterial wall stiffening, and a narrowing of conduit artery diameter. All these factors contribute to the poor health prognosis in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Review study 36 has suggested that prolonged uninterrupted periods of being sedentary results in insufficient skeletal muscle contractions, which suppresses lipoprotein lipase activity, blunts triglyceride uptake, reduces HDL-C levels and glucose load, and increases insulin resistance. In addition, prior bedrest studies 38, 39 demonstrated that prolonged sedentary time leads to impaired vascular function manifest as endothelial dysfunction, arterial wall stiffening, and a narrowing of conduit artery diameter. All these factors contribute to the poor health prognosis in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, findings in this study set ESRD as a condition entailing a risk for muscle function impairment similar or higher than that of other severe chronic disease like peripheral artery disease or a neurologic disease like multiple sclerosis. Along with higher rmVO 2 , physical inactivity and sedentarism induce vascular deconditioning, with reduced endothelium-dependent vasodilatation and increased arterial stiffness and vasoconstriction [21,22] , alterations which are almost universal in ESRD patients [23] . On the other hand, muscle deconditioning attributable to the burden of ESRD -including muscle wasting, anemia and other comorbidities -and the resulting sedentary lifestyle are recognized as a prevalent, major clinical problem in ESRD patients on dialysis [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Intensity of exercise may also affect arterial stiffness, which was shown to decrease significantly after high intensity interval exercise but not moderate continuous exercise [65]. Conversely, short-term bed rest (five days) resulted in decreased FMD and increased arterial stiffness [56]. Future work should identify the cause and time course of the transient increase in arterial stiffness parameters following WI.…”
Section: Discussionmentioning
confidence: 98%